Asthma attacks and deprivation: gradients in use of mobile emergency medical services. Issue 11 (14th October 2008) - Laurent, O; Filleul, L; Havard, S; Deguen, S; Declercq, C; Bard, D
Abstract : Background: To test whether rates of emergency telephone calls for asthma attacks are associated with contextual socioeconomic deprivation in the Strasbourg metropolitan area (France). Methods: Two mobile emergency medical service networks provided all data for 2000–2005 about emergency calls for asthma attacks, georeferenced by census block. Contextual deprivation was measured for each census block by a composite index, constructed by principal component analysis. Emergency call rates were calculated for each census block and for different age groups. Empirical Bayesian smoothing was used to reduce the instability of outlying rates. Results: Positive spatial autocorrelation was detected in both the health and the socioeconomic datasets. In all age groups, rates of calls for asthma attacks increased linearly with deprivation. Correlation coefficients between these two factors varied according to age group: 0.53 for the group aged 0–9 years, 0.46 for 10–19 years, 0.65 for 20–39 years, 0.70 for 40–64 years, 0.68 for 65 and older, and 0.77 for the age-standardised incidence ratio. These correlation coefficients were highly significant (p<0.01), even after spatial autocorrelation was taken into account. Conclusion: The socioeconomic gradients observed are consistent with those observed for severe forms of asthma and asthma hospitalisations in Western countries.